1 times -2 = -2.
Chat with our AI personalities
x^-1 * x^-1 =x^(-1 + -1) =x^-2 or alternatively: 1/x times 1/x =1/x^2 (1/x^2) is the same as (x^-2)
When a negative number is raised to an even power, the result is always positive. Therefore, (-1)^4 equals 1. This is because multiplying a negative number by itself an even number of times will always result in a positive value.
1/3 x -2 = -2/3
240
The answer is "negative three halfs." (- 3/2) or _ 1 1/2 The equation is: -2/3 (x) = 1 -x = 3/2 x = -3/2 (aka negative one and one half)